Copper-catalyzed acyltrifluoromethylation of alkenes: rapid access to trifluoroethyl indanones and related compounds. Issue 48 (31st May 2017) - Liu, Zhicheng; Bai, Yihui; Zhang, Jian; Yu, Yongqi; Tan, Ze; Zhu, Gangguo
Abstract : Copper-catalyzed acyltrifluoromethylation of alkenes is described, affording trifluoroethyl indanones and related cyclic ketones in promising yields with excellent diastereoselectivity. Abstract : Copper-catalyzed acyltrifluoromethylation of alkenes has been developed for the first time, affording trifluoroethyl indanones and related cyclic ketones in promising yields with excellent diastereoselectivity. The fast incorporation of CF3 and indanone into a single molecule renders it an efficient and valuable tool for the synthesis of biologically active compounds.